Sodium-glucose cotransporter-2 inhibitors use and the risk of gout: a systematic review and meta-analysis - Lai, Shih-Wei; Hwang, Bing-Fang; Kuo, Yu-Hung; Liu, Chiu-Shong; Liao, Kuan-Fu (Frontiers in Endocrinology, 2023)
Objective To assess the relationship between use of sodium-glucose cotransporter-2 inhibitors (SGLT2i) and the risk of gout among patients with type 2 diabetes mellitus (T2DM). Methods A systemic review and meta-analysis were designed by reviewing articles published between 2000 January 1 and 2022 December 31 using PubMed system and Web of Science system based on the PRISMA 2020 guidelines. The end point of interest was gout (including gout flares, gout events, starting uric-acid lowering therapy and starting anti-gout drugs use) among patients with T2DM using SGLT2i versus not using SGLT2i. A random-effects model was utilized to measure the pooled hazard ratio (HR) with 95% confidence interval (CI) for the risk of gout associated with SGLT2i use. Results Two prospective post-hoc analyses of randomized controlled trials and 5 retrospective electronic medical record-linkage cohort studies met the inclusion criteria. The meta-analysis demonstrated that there was a decreased risk of developing gout for SGLT2i use as comparing with non-use of SGLT2i among patients with T2DM (pooled HR=0.66 and 95%CI=0.57-0.76). Conclusions This meta-analysis demonstrates that SGLT2i use is associated with a 34% decreased risk of developing gout among patients with T2DM. SGLT2i may be the treatment options for patients with T2DM who are at high risk of gout. More randomized controlled trials and real-world data are needed to confirm whether there is a class effect of SGLT2i for the risk reduction of gout among patients with T2DM.